2011
DOI: 10.1002/adsc.201100050
|View full text |Cite
|
Sign up to set email alerts
|

An Easy Entry to Optically Active Spiroindolinones: Chiral Brønsted Acid‐Catalysed Pictet–Spengler Reactions of Isatins

Abstract: Abstract:The first catalytic asymmetric PictetSpengler reaction of isatins is presented. BINOLderived phosphoric acids were found to be competent catalysts for this transformation, giving challenging spirooxindole structures bearing a quaternary stereocentre with generally good results. The 1,2,3,4-tetrahydro-b-carboline products (spiroindol-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(55 citation statements)
references
References 72 publications
(15 reference statements)
1
54
0
Order By: Relevance
“…8c,13 We have previously shown that this reaction is efficiently catalyzed using Lewis acidic metal salts, thioureas, or BINOL-derived chiral phosphoric acids. The 5-fluorospiroindolone 16b was prepared using a BINOL-derived phosphoric acid catalyst to demonstrate the enantioselective synthesis and evaluate the retention of enantiomeric excess in the CuAAC reaction.…”
Section: Resultsmentioning
confidence: 99%
“…8c,13 We have previously shown that this reaction is efficiently catalyzed using Lewis acidic metal salts, thioureas, or BINOL-derived chiral phosphoric acids. The 5-fluorospiroindolone 16b was prepared using a BINOL-derived phosphoric acid catalyst to demonstrate the enantioselective synthesis and evaluate the retention of enantiomeric excess in the CuAAC reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy examples are Povarov reactions, O-alkylations, Pictet-Spengler reactions or benzidine rearrangement [73][74][75][76]. Chiral BA have shown particularly successful performances in the acetalisation reaction [77][78][79].…”
Section: Brønsted Acid Catalysismentioning
confidence: 99%
“…Molecules bearing a spirocyclic oxindole ring (spirooxindole) system are widely found in nature and have recently attracted significant attention because of their unique structure and broad biological activities such as antitumor , antitubercular , antimicrobial , antifungal , antimycobacterial , antimalarial , and antioxidant and can also serve as synthetic intermediates for alkaloids and many kinds of pharmaceuticals or drug precursors . Furthermore, organophosphorous heterocycles, especially an oxazaphosphorines structure, such as cyclophosphamide, ifosfamide (Fig.…”
Section: Introductionmentioning
confidence: 99%